(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to (know the difficulties of practical application in the College of Education - Al-Mustansiriya University from the point of view of students of the Department of Holy Qur’an Sciences and Islamic Education). (The questionnaire), which is the most appropriate for the current research, and it contained six fields.The researcher applied the tool to the mentioned sample and extracted the results, then the researcher interpreted it in two areas: first: arranging the fields and interpreting them in general, as the researcher arranged the fields in descending order according to the severity of each of them, and second: arranging the difficulties in descending order according to the severity of each of them and according to their fields and interpreting the first (higher) quadrant And the last (low) quarter.